Quantifying connectivity and its effects on sediment budgeting for an agricultural basin, Chesapeake Bay Watershed, United States. Issue 12 (28th December 2022) - Clifton, Zachary J.; Cashman, Matthew J.; Gellis, Allen C.; Katoski, Michelle P.; Nibert, Lucas A.; Noe, Gregory B.
Abstract: Excessive sediment runoff as a result of anthropogenic activities is a major concern for watershed ecologic health. This study sought to determine the sources, storage, and delivery of sediment using a sediment budget approach for the predominantly pasture and forested Smith Creek watershed, Virginia United States, a tributary to the Chesapeake Bay. Utilizing a novel combination of the Universal Soil Loss Equation (USLE) model and an index of connectivity along with field surveys of channels, this study indicated that streambanks and pastures were major sources of sediment. Overestimation of fine‐grained sediment flux exported from the watershed according to this study's models (3811 Mg/year) compared to export measured at the outlet (2918 Mg/year) most likely indicates underestimation of storage in the watershed from unaccounted for geomorphic features (ponds, toe slopes, and colluvial slopes). Sediment budget results indicating that streambanks are a major source of sediment in the watershed support previous sediment fingerprinting results and provide a framework for managers to address the sediment problem in Smith Creek and similar tributaries to the Chesapeake Bay. Abstract : This study sought to determine the sources, storage and delivery of sediment using a sediment budget approach for the predominantly pasture and forested Smith Creek watershed, Virginia United States, a tributary to the Chesapeake Bay. Utilizing a novel combination of the Universal Soil Loss Equation (USLE) model and an index of connectivity along with field surveys of channels, this study found that streambanks and pastures were major sources of sediment. Sediment budget results indicating that streambanks are a major source of sediment in the watershed support previous sediment fingerprinting results and provide a framework for managers to address the sediment problem in Smith Creek and similar tributaries to the Chesapeake Bay.